Study of Physicochemical Characteristics of Kaolin from Belitung Regency - Nurul Izzah Pasi; Marline Abdassah Bratadireja; Anis Yohana Chaerunnisa (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Kaolin is one of the abundant clay minerals on earth which has been widely used in various industries. kaolin as a raw material in drugs manufacturing must comply several requirements in Pharmacopoeia such as not exceeding the heavy metal content limits. In this study the analysis of heavy metal content (Pb, Sn, and As) was carried out on natural kaolin obtained from 3 different locations in Belitung regency. Testing of the brightness and particle size is also carried out to increase the value of kaolin as a pharmaceutical excipient. The highest recovery from kaolin was obtained in sample 3 which was 67.78%, while kaolin 1 and 2 which was 66.54, and 64.20%. Based on the results of heavy metal testing it is known that kaolin 1, 2, and 3 have a Pb content of 55.2, 0.0458 and 44.0 ppm, and As content of 1.05, 78.3, and 0.761 ppm. Whereas the Sn mean metal is only found in kaolin 2 which is 0.0034. White degree test results show that kaolin 1, 2 and 3 have a high brightness, namely 92.94%, 93.00%, 91.16%. From the results of particle size testing shows that all kaolin samples have size <2 μm.Keywords: Characterization of Minerals, Heavy Metals, Kaolin